Apologetics and Cultural Context: a Case Study. (11th June 2021) - Pickering, David
Abstract : This essay interrogates the relationship between the content of an apologist's message and contingent cultural factors. It does so by using the work of G.K. Chesterton as a case study. It explores two major features of his apologetics project in relation to cultural and social issues of his time. The essay concludes by discussing possible lines of enquiry in contemporary apologetics which might be inspired by the study of Chesterton's work.